Tinjauan Literatur pada pengaruh Profitabilitas dan Leverage Terhadap Tax Avoidance - Anita Yohana; Ari Eddy Sarwono; Fadjar Harimurti (Jurnal Publikasi Ekonomi dan Akuntansi, 2025)
Tax avoidance is a common practice carried out by companies to reduce their tax obligations legally. Based on previous studies, profitability and leverage variables are some of the factors that can influence a company's decision to avoid taxes. This study aims to collect new information and evaluate the influence of profitability and leverage on tax avoidance using a qualitative literature review research method from journals indexed in SINTA and Google Scholar in the last five years. The literature reviewed shows that profitability has a significant positive or significant negative effect on tax avoidance. On the other hand, leverage also has an effect on tax avoidance, either significantly positive or significantly negative. There are even research results that reveal that the two variables do not affect tax avoidance. The results of this study indicate that profitability has a significant positive effect on tax avoidance while the leverage variable does not affect tax avoidance